HUBUNGAN PENGETAHUAN, SIKAP, DAN PENGAWASAN DENGAN PERILAKU PENGGUNAAN APD PADA PEKERJA KONSTRUKSI - Audina, Salwa Azara; Andriyani, Andriyani; Triana Srisantyorini (Cahaya Ilmu Bangsa Institute, 2025)
The implementation of occupational safety and health (OHS) principles in Indonesia is still not optimal, as reflected in the high number of work accidents. One important aspect in OHS is the use of Personal Protective Equipment (PPE), which is the last step in the risk control hierarchy after efforts to eliminate, substitute, engineer, and administrative control are ineffective. The purpose of this literature review is to evaluate various factors related to the behavior of PPE use among workers. This study uses a literature review method with data collected from various sources such as ProQuest, PubMed, ResearchGate, SagePub, and Google Scholar, in the period 2018 to 2025. The article selection process was carried out using the PRISMA flow diagram, which includes the stages of identification, screening, eligibility assessment, and inclusion. Search keywords include